REMEDIASI MISKONSEPSI SISWA PADA MATERI MAGNET MENGGUNAKAN WAWANCARA KLINIS DALAM BAHASA MELAYU SAMBAS - Aspian, Hapit; Tandililing, Edy; Mahmuda, Diah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aimed to apply clinical interviews using mother tongue as an effort to remediate the studentsâ€™ misconceptions of SD Negeri 18 Enggadang about magnet. The research form used was pre-experimental one group pre-test post-test design. Data collection tools are 9 multiple choice questions with 3 alternative answers. The sample of this study was the fifth-grade students of SD Negeri 18 Enggadang consisting of 19 people who were chosen by saturated sampling technique where all members of the population were used as samples. Based on the results, the average percentage of studentsâ€™ misconceptions at pre-test was 54.4% and the average percentage of students' misconceptions at post-test was 5.3%. The decrease in the number of student misconceptions was 28 misconceptions. Therefore, remediation using clinical interviews can be used to correct student misconceptions on magnetic subject. Clinical interviews are expected to be used as an alternative remediation activity in order to overcome misconceptions experienced by students.Keyword: Remediation, Misconception, Clinical Interview, Magnet.Â